A 'Somewhat Eccentric Preacher'; the Reverend Richard Hale of Harewood. (August 2015) - Lynch, Karen
Abstract : In December 1810 Lord Harewood hosted an unusual event in his London townhouse. The visitors were eminent men, leaders in their field, but the guest of honour was apprehensive. Beneath the elegant Adam ceilings, the baron's nephew, the Revd Richard Hale, was about to have his leg amputated at the knee. The operation also marked the end of Hale's life as a man of fashion enjoying a busy social whirl of parties, balls and race meetings whilst curates attended to his parishes. During his recuperation he vowed to devote himself to God and his parish, thus beginning four decades as one of the more colourful clergymen of the nineteenth century.